PENGARUH GAME EDUKATIF WORDWALL TERHADAP MINAT BELAJAR SISWA PADA MATERI PENGARUH GAYA TERHADAP BENDA KELAS IV SD NEGERI 115 PEKANBARU - Gita Cahya Ramadhani; Fitriyeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Wordwall educational game on students' learning interest in the material of the influence of force on objects in grade IV of SD Negeri 115 Pekanbaru. This study uses a quantitative approach with a pre-experimental method through a One-Group Pretest-Posttest Design. The research sample consisted of 33 grade IVB students selected using a purposive sampling technique. Data collection techniques were carried out using a learning interest questionnaire given before and after the implementation of the Wordwall educational game. The results showed an increase in students' learning interest after the use of Wordwall media. The average pretest score of 74% increased to 91% in the posttest with an increase of 17.21%. In addition, the results of the paired sample t-test analysis showed a significance value (Sig. 2-tailed) of 0.000 <0.05 and a calculated t value of -8.340 which indicated a significant difference between the pretest and posttest results. Thus, it can be concluded that the use of the Wordwall educational game has a positive and significant effect on students' learning interest in science lessons on the effect of force on objects in fourth-grade students of SD Negeri 115 Pekanbaru.